Perspektywy rynku kredytowania nieruchomości w Polsce - Półtorak, Bogusław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
On Polish mortgage market dominate universal banks. Above all they give traditional credit mortgages. There is not any e.g. reverse mortgage in their offers. Increase of Polish consumption creditability caused growing up demand on mortgages. Universal banks financing their credit action using short-term deposits what causes increase of bank risk. So why supervision limited conditions of providing mortgages which are given by universal banks. Developing mortgage market (like in other EU countries) needs financing through emission of mortgage bonds and securitisation of financial assets (Mortgage Backed Securities). Thanks to it cost of mortgage may be lower. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 155-165